National identity, inclusion and exclusion. An empirical investigation - Lödén, Hans (Sens public)

(untitled) (Département des littératures de langue française, 2010)
Results from a research project conducted among 1000 secondary school students in Sweden are used for discussing superordinate national identity as a means for immigrants’ integration into democratic politics and the challenges this may present for social science education. The theoretical point of departure is taken within social identity theory, with emphasis on its findings concerning relationships between superordinate and subgroup identities. It is suggested that a superordinate national identity perceived as inclusive, by immigrants and the native population, would be conducive to integration into democratic nation-states. Such states are seen as the dominant organizational form for democratic politics in the foreseeable future. It is argued that command of the dominant language of society is most important of the inclusive criteria. Other such criteria are respect of the state's political institutions and feelings of belonging to the country where you live. The argument is supported by data, showing a majority of secondary school students – of self-identified 'Swedish' or non-'Swedish' backgrounds – in favour of inclusive criteria for a 'Swedish' national identity.